REPERCUSSIONS OF THE FINANCIAL CRISIS ON MARKETING PERFORMANCE-AN APPLIED STUDY IN FURAT KARBALA COMPANY FOR THE MANUFACTURE OF THERMOS TONE - Maydia Hassan madhi; Zina Mohammed Sebti; Nidhal Abdullah Yaseen Almaliki (Scholars Digest Publishing, 2023)
The economy faced one of the most challenging crises in its modern history, which led it to bear the repercussions of the financial crisis, which turned into an economic crisis that had adverse effects on various countries of the world and economic sectors, and among these sectors is the marketing sector, The marketing sector is one of the necessary sectors in the marketing of financial services that are related to the development goals. Therefore, improving the quality of marketing services and striving to develop the specifications of the reality of customer satisfaction helps in enhancing the marketing sector. This study is divided into five parts, the first part deals with the research methodology and the second part deals with the impact of the financial crisis, the third section dealt with marketing and its historical development, and the fourth section dealt with the practical side of the research and was divided into two requirements. for the manufacture of the mudstone. The second requirement is the presentation and analysis of data and statistics. The fifth topic dealt with a set of conclusions and recommendations.
Keywords: reflections, financial crisis, marketing performance.